Strategi Komunikasi Guru untuk Meningkatkan Keterampilan Bekerja Sama Siswa Kelas IV pada Mata Pelajaran IPAS di SDN Model Mataram - Robbi Maulana; Asrin; Mansur Hakim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the teacher's communication strategies in Integrated Science and Social Studies (IPAS) learning, describe the collaborative skills of fourth-grade students, and analyze the role of teachers' communication strategies in developing students' collaborative skills in the IPAS subject at SD Model Mataram. This study employed a qualitative approach using a case study design. The research participants consisted of one fourth-grade teacher and 17 fourth-grade students. Data were collected through passive participant observation, semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through technique, source, and time triangulation. The findings revealed that the teacher's communication strategies comprised five dimensions: clarity of instructional delivery, the use of adaptive language, constructive feedback, persuasive communication, and group communication management. Students' collaborative skills encompassed active participation, respect for others' opinions, responsibility, group communication, and conflict resolution. The study concludes that teachers' communication strategies play a pivotal role in fostering students' collaborative skills by creating a conducive learning environment and providing systematic and well-planned guidance